Study and optimization of epitaxial films of Cr and Pt/Cr bilayers on MgO. (27th December 2019) - Rinaldi, C; Asa, M; Chrastina, D; Hart, J L; Taheri, M L; Pallecchi, I; Marré, D; Cantoni, M
Abstract: We report a systematic study of the fabrication and chemical and structural characterization of epitaxial Cr films and Pt/Cr bilayers on MgO substrates. Cr films of different thicknesses were grown by molecular beam epitaxy at 373 K and then post-annealed at different temperatures. These films are chemically stable, present a well-ordered tetragonal structure, with only a low degree of oxidation distributed throughout the films. The lattice parameter can be finely tuned by varying the film thickness and the post-annealing temperature, as the elastic energy is progressively relaxed by edge dislocations, so that the film can approach the structural and electrical properties of bulk chromium. Moreover, the chemical and structural properties of Cr are not affected by a Pt capping layer, which grows in a well-ordered Pt[1 1 0]||Cr[1 0 0] orientation, holding potential for applications in recently proposed Pt/Cr-based antiferromagnet spintronics and for the realization of epitaxial Pt films on MgO by using a thin buffer layer of chromium.